Immunoinformatics approach to Design a Self-assembling Multi-epitope Nanovaccine targeting Enterotoxigenic Escherichia coli (ETEC) Non-canonical Antigens - Almazan, Debrah Jannsen DJ N., Arcan, Stephen Kyle C., Bandahala, Aldam K., Palanca, Aracelle H. 4 0 16; 5
Abstract Enterotoxigenic Escherichia coli (ETEC) is the major etiological agent of diarrhea predominantly affecting children, and travelers in developing countries. Though infections have so far been contained, the emergence of antibiotic resistant strains still threatens the lives of many, calling for the development of avenues to combat these strains. Here, an immuninformatics pipeline was employed to construct a potential nanovaccine for ETEC which included a microbiology, molecular biology, and bioinformatics workflow to design, characterize and analyze the nanovaccine. Gene amplification of E. coli ATCC 25922 revealed functionally related genes. Their gene products, esterase and TVP38/TMEM64 family transmembrane protein, were used for subsequent bioinformatics analysis. Epitope prediction reported 11 cytotoxic T-lymphocyte (CTL), three helper T-lymphocyte (HTL), and seven B-cell lymphocyte (BCL) epitopes, from which a final 15.53 kDa, positively charged, thermostable, hydrophilic, and soluble 139-residue nanovaccine was designed. Structural validation assessed its overall quality, reporting 85.71% ERRAT and 21.58% Verify3D results attributed to its lack of crystal structure, and acceptable stereochemical quality through PROCHECK. Molecular docking simulation of the nanovaccine construct and TLR2 receptor yielded a significant binding energy of -926.5 kcal/mol. Molecular dynamics simulation elucidated the structural stability of the complex using trajectory analyses. Increasing immunoglobulins, pro-inflammatory cytokines, and immune cell concentrations were recorded using C-Imm-Simm immune simulation, indicating immunogenicity. This study presented a novel self-assembling multi-epitope nanovaccine with notable structural stability and immunogenicity that can be utilized in future in vitro and in vivo studies for further analysis Keywords: Enterotoxigenic Escherichia coli, immunoinformatics, self-assembly, multi-epitope vaccine
Undergraduate Thesis: (BS in Biology major in Cell and Molecular Biology) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2